PUBLIC PARTICIPATION IN DEVELOPING SOCIETY - Md Zan, Zainal; Hj Rofie, Mohamad Khadafi; Ngah, Kamarudin (Universitas Islam Negeri Alauddin Makassar, 2015)
The development and modernity have constrained the society life lately with assorted issues related to economy, social, and any other physical aspects. Therefore, prosperous development and considering society needs are important to achieve. Behind the design and ‘top-down’ growth, the ‘bottom-up’ approach application should not be ignored. The development design approach imposed from the lower community level is important in line with the advanced justice and democracy concepts. Public participation in improving society is one of the approaches which can guarantee the tangible society welfare in some countries. The public participation can assist the society to attain their willing and necessity through voting and shaping or adapting their ideas. Thereby, this paper investigated about the public participation in developing society.